Nature Reserve Selection Problem: A Tight Approximation Algorithm - Bordewich, M.; Semple, C. (IEEE/ACM transactions on computational biology and bioinformatics, 2008)
The nature reserve selection problem is a problem that arises in the context of studying biodiversity conservation. Subject to budgetary constraints, the problem is to select a set of regions to be conserved so that the phylogenetic diversity of the set of species contained within those regions is maximized. Recently, it has been shown in a paper by Moulton et al. that this problem is NP-hard. In this paper, we establish a tight polynomial-time approximation algorithm for the Nature Reserve Section Problem. Furthermore, we resolve a question on the computational complexity of a related problem left open by Moulton et al.